Chemoprevention of aflatoxin B1-induced genotoxicity and hepatic oxidative damage in rats by kolaviron, a natural biflavonoid of garcinia kola seeds (2005)
The chemopreventive effects of kolaviron, a natural antioxidant biflavonoid from the seeds of Garcinia kola, on aflatoxin B1 (AFB1)-induced genotoxicity and hepatic oxidative damage was investigated in rats. Kolavironmadministered orally at a dose of 200 mg/kg once a day for the first 2 weeks and then 100 mg/kg twice a day for the last 4 weeks of AFB1 (2 mg/kg, single dose, intraperitoneal) treatment reduced the AFB1-increased activities of aspartate amino transferase (AST), alanine amino transferase (ALT) and gamma glutamyltransferase (c-GT) by 62%, 56% and 72% respectively. Malondialdehyde (MDA) formation and lipid hydroperoxide (LHP) accumulation were observed in the livers of AFB1-treated rats. Kolaviron significantly reduced the AFB1-induced MDA and LHP formation. Vitamins C and E were protective in reducing the increase in the activities of AST, ALT and c-GT as well as lipid peroxidation caused by AFB1 (P < 0.01). Administration of rats with kolaviron alone resulted in significant elevation in the activities of glutathione S-transferase, uridyl glucuronosyl transferase and NADH:quinone oxidoreductase by 2.45-, 1.62- and 1.38-folds respectively. In addition, kolaviron attenuated the AFB1-mediated decrease in the activities of these enzymes (P < 0.01). Pretreatment of rats with kolaviron, vitamins C and E alone did not exert genotoxicity assessed by the formation of micronucleated polychromatic erythrocytes (MNPCEs) (P> 0.05). Co-treatment of rats intraperitoneally with kolaviron (500 mg/kg) 30 min before and 30 min after AFB1 (1 mg/kg) administration inhibited the induction of MNPCEs by AFB1 (P < 0.001) after 72 h. While vitamin C was effective in reducing AFB1- induced MNPCEs formation, vitamin E did not elicit any antigenotoxic response. These results indicate kolaviron as effective chemopreventive agent against AFB1-induced genotoxicity and hepatic oxidative stress. Thus kolaviron may qualify for clinical trial in combating the menace of aflatoxicosis in endemic areas of aflatoxin contamination of foods.